Suppression of Akt1-β-catenin pathway in advanced prostate cancer promotes TGFβ1-mediated epithelial to mesenchymal transition and metastasis. (28th August 2017) - Gao, Fei; Alwhaibi, Abdulrahman; Sabbineni, Harika; Verma, Arti; Eldahshan, Wael; Somanath, Payaningal R.
Abstract: Akt1 is essential for the oncogenic transformation and tumor growth in various cancers. However, the precise role of Akt1 in advanced cancers is conflicting. Using a neuroendocrine TRansgenic Adenocarcinoma of the Mouse Prostate ( TRAMP ) model, we first show that the genetic ablation or pharmacological inhibition of Akt1 in mice blunts oncogenic transformation and prostate cancer (PCa) growth. Intriguingly, triciribine (TCBN)-mediated Akt inhibition in 25-week old, tumor-bearing TRAMP mice and Akt1 gene silencing in aggressive PCa cells enhanced epithelial to mesenchymal transition (EMT) and promoted metastasis to the lungs. Mechanistically, Akt1 suppression leads to increased expression of EMT markers such as Snail1 and N-cadherin and decreased expression of epithelial marker E-cadherin in TRAMP prostate, and in PC3 and DU145 cells. Next, we identified that Akt1 knockdown in PCa cells results in increased production of TGFβ1 and its receptor TGFβ RII, associated with a decreased expression of β-catenin. Furthermore, treatment of PCa cells with ICG001 that blocks nuclear translocation of β-catenin promoted EMT and N-cadherin expression. Together, our study demonstrates a novel role of the Akt1-β-catenin-TGFβ1 pathway in advanced PCa. Highlights: Akt1 deficiency blunts oncogenic transformation and prostate cancer growth. Akt1 inhibition in advanced prostate cancer promote metastasis. Akt1 loss in advanced prostate cancer promote epithelial-to-mesenchymal transition. Akt1 suppression in advanced prostate cancer suppress β-catenin expression. β-catenin inhibition in PC3 and DU145 cells promote mesenchymal transition.